Effect of thermal stress on the life of DC link capacitors for smart grid - Xiao-Wu Sun; Ying Qiao; Yin-Da Li; Chong-Feng Cao; Xiang-Ming Guo (Scientific Reports)
Abstract Thermal stress is an important factor affecting the life of a DC link capacitor (DCLC). However, relevant studies on thermal stress mechanism directly influencing the lifetime of the capacitor are rarely reported. In this paper, the heat setting and thermal stress of DCLC has been analyzed, and the relevant experimental platforms have been developed to evaluate the breakdown strength of DCLC at two heat setting temperatures (HSTs). Simultaneously, the life aging analysis of DCLC at different HSTs and the life aging tests at various temperatures were also executed to attain insights into the influence of thermal stress on the lifetime of DCLC. The results showed that the stress caused by heat setting and operating temperature influenced the breakdown voltage capability and the lifetime of DCLC. With an increase in HST by 5 °C, a step-increase in the withstand voltage capability of DCLC from 7,000 V to 7,200 V was observed that demonstrated an enhancement of 2.86% in the breakdown strength performance. Correspondingly, the lifetime of DCLC with a capacitance change rate of -3% enhanced from 1,500 h to 1,700 h. However, severe deterioration in the life span of DCLC from 4,200 h to 500 h was observed with an increasing operating temperature from 55 °C to 85 °C, respectively. The lifetime could be enhanced by increasing the HST as well as reducing the operating temperature. The presented results could be termed a harbinger for industrial production of high-performance DCLC with enhanced lifetime that augers well for high-power applications.